Prevalence of Hypothyroidism in Hemi-thyroidectomy Cases in a Tertiary Care Hospital of Chitwan, Nepal - Bhandari, Chhanya; Paudel, Sanjaya; Sharma, Bibek; Adhikari, Sabin; Upadhyay, Hari Prasad (Journal of Bharatpur Hospital, 2025)
Background Hypothyroidism following hemithyroidectomy surgery has a variable incidence. The purpose of the present study was to determine the prevalence and the risk factors of hypothyroidism following hemithyroidectomy surgery.MethodsThis analytical cross-sectional study was conducted among euthyroid patients who underwent hemithyroidectomy between August 2024 and April 2025 for benign disease in College of Medical Sciences Teaching Hospital, Bharatpur, Chitwan, Nepal. The prevalence of hypothyroidism (thyroid stimulating hormone (TSH) levels > 4.5 micro-IU/L) was analyzed. Factors like preoperative TSH level and gender associations were evaluated for the development hypothyroidism postoperatively.  Data was analyzed using Students t test. p-value